Peningkatan Mental Health Manajemen Keuangan Untuk Cerdas Investasi Masa Depan Generasi Z: Improving Mental Health Financial Management For Smart Future Investment Of Generation Z - Reviandani, Wasti (JURNAL PENGABDIAN MANAJEMEN, 2026)
Mental health and financial management are two interrelated aspects that play an important role in shaping the financial behavior of Generation Z. The rapid development of digital technology and the ease of access to online-based financial services have increased consumptive behavior among students, which may lead to financial pressure and mental health problems. This condition indicates the need for early education so that young generations are able to manage their finances wisely and sustainably. This community service activity aimed to improve the understanding of students and teachers at SMA Muhammadiyah 10 Gresik as the community partner regarding the importance of mental health in financial decision-making, as well as to foster awareness of saving and investing from an early age. The community service methods were implemented through community education activities, including lectures, interactive discussions, and simple financial budgeting training. The results showed an improvement in participants’ understanding of controlling consumptive behavior, preparing more structured financial planning, and recognizing halal investment concepts for beginners. These results are considered important as a preventive effort to shape healthy and sustainable financial behavior, thereby supporting the development of a young generation that is mentally and financially intelligent